Can microplastics in offshore waters reflect plastic emissions from coastal regions?. (December 2022) - Ding, Yongcheng; Zou, Xinqing; Yuan, Feng; Chen, Hongyu; Wang, Chenglong; Fan, Qinya; Fu, Guanghe; Yu, Wenwen
Abstract: Marine microplastic pollution is a major environmental challenge that threatens marine ecosystems and human health. Several models have been used to calculate and predict the theoretical amount of plastic waste discharged into the sea by coastal countries. Unlike earlier theoretical models of source discharge, we used the method of data normalisation to focus on the actual distribution of microplastics and their potential ecological risk in offshore surface waters. Our findings indicate that the average normalised abundance of microplastics in near-shore region of Bohai Sea was greater than the average normalised abundance of microplastics in the seas near the Yangtze River Delta urban agglomeration and the Pearl River Delta urban agglomeration. Moreover, the average amount of plastic waste discharged from terrestrial sources to the ocean per kilometre exhibited the following order: Bohai Rim urban agglomeration (150.90) (tonnes km −1 ) < the Pearl River Delta urban agglomeration (274.30) (tonnes km −1 ) < Yangtze River Delta urban agglomeration (577.44) (tonnes km −1 ). Further, the average microplastics abundance in offshore areas of different countries and the amount of plastic discharged per kilometre of the coastline were significantly negatively correlated, implying that microplastics were not necessarily abundant in coastal areas where large amounts of plastic are discharged into the sea. Hydrodynamic conditions had the greatest influence on the distribution of microplastics in offshore surface waters. The transport of nutrient salts from terrestrial areas to offshore waters was also influenced by hydrodynamics, with enrichment patterns in offshore areas exhibiting similar to those of microplastics. Therefore, when the offshore microplastic accumulation area overlapped with the nutrient salt enrichment zone, the health risk associated with the consumption of edible fish from offshore communities increased. In view of these findings, coastal countries must implement policies to reduce marine plastic waste emissions and develop management strategies based on their local pollution levels. Graphical abstract: Image 1 Highlights: There's a mismatch between theoretical plastic discharges and MPs distribution. MPs aren't necessarily abundant where large amounts of plastic input into the sea. Hydrodynamic conditions had the greatest influence on the MPs distribution. Health risk of offshore fish consumption increases when MPs overlaps with nutrient.